Aptamer-conjugated gold nanoparticles enable oligonucleotide delivery into muscle stem cells to promote regeneration of dystrophic muscles - Francesco Millozzi; Paula Milán-Rois; Arghya Sett; Giovanni Delli Carpini; Marco De Bardi; Miguel Gisbert-Garzarán; Martina Sandonà; Ciro Rodríguez-Díaz; Mario Martínez-Mingo; Irene Pardo; Federica Esposito; Maria Teresa Viscomi; et al. (Nature Communications)
Abstract Inefficient targeting of muscle stem cells (MuSCs), also called satellite cells, represents a major bottleneck of current therapeutic strategies for muscular dystrophies, as it precludes the possibility of promoting compensatory regeneration. Here we describe a muscle-targeting delivery platform, based on gold nanoparticles, that enables the release of therapeutic oligonucleotides into MuSCs. We demonstrate that AuNPs conjugation to an aptamer against α7/β1 integrin dimers directs either local or systemic delivery of microRNA-206 to MuSCs, thereby promoting muscle regeneration and improving muscle functionality, in a mouse model of Duchenne Muscular Dystrophy. We show here that this platform is biocompatible, non-toxic, and non-immunogenic, and it can be easily adapted for the release of a wide range of therapeutic oligonucleotides into diseased muscles.